The relation between self-regulated learning, academic performance of graduate student - Madihie, Amalia; Mos, Zarifah (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
The purpose of this study is to discover possible relationships between self-regulated learning with graduate students’ academic performance. Eighty graduate students from the Learning Sciences Programme and Human Resources Programme at Faculty of Cognitive Sciences and Human Development were randomly selected. Motivated Strategies for Learning Questionnaire (Pintrich, 1991) was piloted and administered. First, the questionnaire was undergone the back-to-back translation (into Malay language version). Two variables that involved in this study were motivation and learning strategies. Academic performance measured to be dependent variable which is the graduate students’ current CGPA. Findings show that there is no relation between motivation and learning strategies with academic performance. Future recommendations are also discussed in this study.